Improving Prediction of Severity of Sepsis in Children: A Single Center trial - Ilham Youssry; Hebatullah Zarea; Hanaa I. Rady; Dina Khedr (Cairo University, Faculty of Medicine, Department of Pediatrics, 2024)
Background: Early diagnosis of sepsis and its severity is essential for timely management to improve patient survival. Aim of the work: define prognostic indicators of mortality in children presenting with sepsis. Materials and Methods: A prospective observational cohort study included 45 children with sepsis admitted to the Pediatric Intensive Care Unit (PICU), Children Hospital, Cairo university. Studied predictors included clinical assessment, modified Sequential Organ Failure assessment m (SOFA) score calculation, age- adjusted quick Sequential Organ Failure assessment (qSOFA), Pediatric Risk of Mortality (PRISM) score and lab investigations, including reticulocyte distribution width (RDW). Results: The age of enrolled children with sepsis ranged between 0.16 - 5 years (median= 1 year), 27 (60 %) of them were males. Of them, 14 (31%) patients died. The mortality among them was predicted by the mSOFA above the cutoff point of 12 had 92% sensitivity, 96% specificity, 92% positive predictive value (PPV), and 96% negative predictive value (NPV) with area under the curve (AUC): 0.97, 95 % confidence interval (CI) 0.93 to 1, the PRISM III score above the cutoff point of 15 had 92% sensitivity, 90 %specificity, 81 % PPV, and 96% NPV with AUC: 0.96, 95 % CI 0.9 to 1, and the RDW above the cutoff point of 21 had 92% sensitivity, 66% specificity, 56% PPV, and 95% NPV with AUC: 0.86, 95 % CI 0.754 to 0.973. The age-adjusted qSOFA failed to predict mortality. Combining the RDW with these scores improved the mortality prediction as the combined RDW to the mSOFA above the cutoff point of 34 showed 100% sensitivity, 90 %specificity, 82 % PPV, and 100% NPV with AUC: 0.97, 95 % CI 0.93 to 1 and the combined RDW to the PRISM III score above the cutoff point of 41 had 92% sensitivity, 96 % specificity, 92 %, PPV, and 96% NPV with AUC: 0.98, 95 % CI 0.96 to 1. Conclusion: RDW combined with mSOFA score above the cutoff point of 34 and PRISM III score above the cutoff point of 41 were sensitive and specific predictors of mortality among children with sepsis. They may be used as indicators for timely referral of children with sepsis from the emergency ward to the PICU.